3D angle interlock woven fabric mechanical tensile strength based on various fabric weft densities / Muhammad Nasrun Faris Mohd Zulkifli and Mohamad Faizul Yahya - Mohd Zulkifli, Muhammad Nasrun Faris; Yahya, Mohamad Faizul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
3D angle interlock is one of many textile woven structures that have shown prominent mechanical tensile strength properties towards technical application such in transportation, structural reinforcement, and sport purposes. This paper intends to show the influence of fabric weft density parameter towards mechanical tensile strength performance of 3D angle interlock woven fabric. The woven fabric samples were fabricated with two different weft densities parameters which were 22 and 25 pick.cm-1 (ppcm). The tensile strength test on woven fabric sample was tested accordingly to the American Standard for Testing and Materials (ASTM). The results revealed that highest fabric weft density at 25 pick.cm-1 contributed to the highest weft crimp percentage at 4.7 % and weft stress performance at 67.2 MPa.